2019
DOI: 10.1093/neuros/nyz377
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Retreatments and Expenditures in Flow Diversion Versus Coiling for Unruptured Intracranial Aneurysm Treatment: A Retrospective Cohort Study Using a Real-World National Database

Abstract: BACKGROUND Flow diverters (FDs) have marked the beginning of innovations in the endovascular treatment of large unruptured intracranial aneurysms, but no multi-institutional studies have been conducted on these devices from both the clinical and economic perspectives. OBJECTIVE To compare retreatment rates and healthcare expenditures between FDs and conventional coiling-based treatments in all eligible cases in Japan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…23,26) Although previous studies included small aneurysms, aneurysms in locations other than the ICA, or FD approaches other than the PED, the reported cost of FD treatment was lower than that for coil embolization, 25,34,35,37,[38][39][40][41] especially when 9 or more coils were required during the coil embolization procedure. 34) However, almost all previous studies reported the costs for the entire hospital stay, including device costs. Coby et al 40) reported a lower cost of implants and of the total procedure in the PED group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,26) Although previous studies included small aneurysms, aneurysms in locations other than the ICA, or FD approaches other than the PED, the reported cost of FD treatment was lower than that for coil embolization, 25,34,35,37,[38][39][40][41] especially when 9 or more coils were required during the coil embolization procedure. 34) However, almost all previous studies reported the costs for the entire hospital stay, including device costs. Coby et al 40) reported a lower cost of implants and of the total procedure in the PED group.…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparisons between coil embolization and FD devices have been reported 23,24,26,[31][32][33][34][35] ; however, this is the only study to directly compare coil embolization and PED treatment in large unruptured paraclinoid aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Retreatment rates among both FDAC and SAC have been shown to be significantly lower than coil embolization alone, with equivocal safety profiles in complex lesions. [ 5 41 42 ] Likely owing to the added benefit of diversion of laminar flow secondary to increased coverage, FDAC has also been reported to have significantly lower retreatment rates as compared to SAC. [ 5 41 42 ] Furthermore, FDAC has shown to be more cost-effective as compared to SAC, likely owing to the decreased number of coils required in dual-modality treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 41 42 ] Likely owing to the added benefit of diversion of laminar flow secondary to increased coverage, FDAC has also been reported to have significantly lower retreatment rates as compared to SAC. [ 5 41 42 ] Furthermore, FDAC has shown to be more cost-effective as compared to SAC, likely owing to the decreased number of coils required in dual-modality treatment. This observation is intuitive, as in SAC, the stent exists to support and prevent prolapse of a large coil mass, which is the primary treatment modality, whereas in FDAC, the coils provide apposition and an immediate safety net for the delayed primary modality of FD.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] There have additionally been multiple studies published comparing CE and FDD approaches for the treatment of IAs since the publication of this previous meta-analysis. [ 17 19 ]…”
Section: Introductionmentioning
confidence: 99%